Western modernization and Marxist political theory: an alternative to lib-eralism Modernização ocidental e teoria política marxista: uma alternativa ao liberalismo - Danner, Leno Francisco (DoisPontos, 2016)
Starting from a critic to Conservative liberalism’s and to new left’s notion of the Western modernization as systemic institutional self-differentiation, self-referentiality and self-subsistence, I argue that such model of systemic theory regarding to the modernization leads both to the systemic institutional autonomy and closure in relation to a direct political praxis and to a binding notion of social normativity, and to the strong institutionalism in political economy and in political institutional praxis. Modernization from a systemic institutional perspective means that each social system has very proper and particular logic and dynamic, which are non-political and non-normative, just technical. So, systemic institutions become depoliticized, delegitimizing a model of radical democratic political praxis which can frame the social systems from an inclusive democratic participation based on a conception of social normativity. As consequence, systemic institutions centralize and monopolize the constitution, the legitimation and the evolution of their own field of social reproduction, closing and autonomizing it regarding the democratic political praxis and the social normativity. I argue that such conservative understanding of the Western modernization can be substituted by the Marxist understanding of the Western modernization, which is based on the comprehension of the society as a totality imbricated in its parts, i.e. the intersection between infrastructure and superstructure as the epistemological-political starting point both to a critical social theory and to a democratic political praxis. Such Marxist theoretical-political starting point enables a critical social theory and a leftist political praxis founded on the politicization of the social systems and their profound linking and rooting in the social world and as a political-normative dynamic.